Research and development of the structure of a vortex heat generator by the method of mathematical modeling - Yaris, Vadim; Kuzyayev , Ivan; Nikolsky , Valeriy; Ved , Viktor; Peter, Chlens; Palagnyuk , Andrii; Lobodenko , Antonina; Reshetnyak , Iryna (Technology audit and production reserves, 2021)
The object of research is a mathematical model of a new design of a vortex heat generator with translational-rotational flow in a variable geometry working space. One of the most problematic areas in the development of new and promising designs of heat generators by the method of physical modeling is the search for its optimal operating-technological and instrumental-design parameters. The implementation of a preliminary analysis of such structures by the method of mathematical modeling will significantly reduce the time and material costs for the development of promising designs of heat generators. The studies of the design of the new vortex heat generator, carried out by the method of mathematical modeling, made it possible to determine the range of its operation, to evaluate the operating-technological and hardware-design parameters that affect the efficiency of work. Studies of the hydrodynamics of the translational-rotational motion of a viscous fluid flow in the working space of a new vortex heat generator with a variable geometry of the working space made it possible to determine the critical velocity and pressure, the influence of the geometric parameters of the device on the generation of vortices that promote cavitation. Model studies were carried out in the range of fluid load changes in the range from 0.001 m3/s to 0.01 m3/s. The study of changes in the velocity field in the channels was carried out for the geometry of the channel with a taper angle from 0° to 25°. The width of the working channel of the space Wn varied in the range of 130, 70 and 40 mm. It has been established that a good axial symmetry and smoothness of the coolant flow in the vortex zone along the swirler screw provides the coolant inlet through a nozzle with a rectangular cross-section. The dependence of the influence of the flow area of the nozzle for introducing the coolant into the vortex zone on the energy efficiency of the vortex apparatus as a whole is found experimentally. The research carried out makes it possible to design vortex heat generators with geometric parameters that meet modern energy efficiency requirements. The geometry of the swirler screw is determined, which increases the efficiency of the heat generator by 35 % in comparison with similar designs of vortex heat generators given in the literature.